Petrophysical evaluation of subsurface reservoir sandstones of Bengal Basin, Bangladesh - Islam, M.A. (Springer Verlag (Germany), 2010)
The present study has been carried out for core and log based petrophysical evaluation of subsurface reservoir sandstones considering at least one well from each of the Kailas Tila, Titas, Bakhrabad and Shahbazpur gas fields of Bangladesh. Core analysis results show that average core porosity, permeability and pore throat values are 20%, 209 mD and 44020 angstrom, respectively. These measured values support that the sandstone reservoirs are categorized as good quality reservoirs. Core porosity values usually exceed thin section porosity. Different cross- plots indicate that permeability is largely dependent on porosity. Permeability and porosity are also dependent on textural parameters that include size, shape, sorting and matrix of the reservoir sandstones. It reveals from both thin section study and different cross plots that diagenetic cements are the main controlling factors of the reservoirs. Quantitative determination of the volume of cements shows that cements have inverse correlation with porosity and permeability. Log based petrophysical parameters include shale volume, porosity, water and hydrocarbon saturation, permeability, moveability index and bulk volume of water. The average values of the mentioned parameters are 20%, 22%, 26%, 74%, 110 mD, 0.28 and 0.05, respectively. The most important parameters are porosity and permeability, which indicate that log porosity exceeds core porosity and log permeability significantly lags behind core permeability. The study also reveals that 23 gas zones covering total thickness of 385 m sandstones mostly posses good quality reservoirs except few moderate quality reservoirs.